Answer:
a square
Step-by-step explanation:
Answer:
x=0 y=-11 (0,-11)
Step-by-step explanation:
1. take what y equals (3x-11) and plug it in for y in the second equation
Should look like this: O= 6x-2(3x-11)-22
2. Then distribute O=6x-6x+22-22
3. Then combine like terms O= 0 the 22's cancel out as well as the x's
x= 0
4. plug 0 in for x in the first equation y=3(0)-11
5. y= -11
6. x=0 y=-11 (0,-11)
Answer:
b
Step-by-step explanation:
Answer:
X is 90 y is 43
Step-by-step explanation:
Answer:
25 hamburgers
88.50/3.50
Step-by-step explanation:
hope this helps
mark me brainly
thanks for the points
anddd
sparkles and love
☆*: .。. o(≧▽≦)o .。.:*☆